PERBANDINGAN ANTARA PEMULIHAN AKTIF (JALAN) DAN PEMULIHAN PASIF (COLD WATER IMMERSION) TERHADAP TINGKAT KELELAHAN OTOT PASCA LATIHAN SUBMAKSIMAL - FAJAR AGASI, IMAM (Jurnal Kesehatan Olahraga, 2016)
Exhausted is one of the factors that is able to decrease the performance of an athlete. It is important to implement a recovery from exhausted effectively and efficiently so when the athlete goes into the field, the athlete has completely recovered and performs at his/her best condition. The goal of this study is to reveal the comparison between passive recovery (cold water immersion) and active recovery in their effects to the post-submaximal exercise muscle exhausted level. This research uses experiment with one group pre-test and post-test design. The number of samples of the research is 10 samples.The result of the research finds the average of lactic in blood at the pre-test is 4.15 mmol/L and 2.26 mmol/L at the post-test (active recovery). In the other hand, the result of the pre-test is 4.75 mmol/L and 2.99 mmol/L at the post test (passive recovery). The average of the lactic acid decrease in the active recovery is 1.89 mmol/L and in the passive recovery is 1.76 mmol/L. According to pre-test data normality test, it is found that ?2table is bigger than ?2count (7,815 > 0,331) and post test (7,815 > 0,386) for active recovery. The passive recovery also reveal that pre test data ?2table is bigger than ?2count (7,815 > 0,164) and post test (7,815 > 0,325), both data have normal distribution. The calculation test of the average difference of lactic acid in the blood after submaximal exercise and after both passive and active recovery is given, the obtained data is tcount 5,449 and the value of ttable 2,262 with level of significanceix0,05 with df = 9 (active recovery) and tcount 3,500 and the value of ttable 2,262 with level of significance 0,05 with df = 9 (passive recovery). Because tcount is bigger than ttabel , it can be concluded that Ho is rejected and Ha is received which means there is an effect between active recovery and passive recovery (cold water immersion) to the decrease of the lactic acid level. From the t count value between active and passive recovery it can be concluded that active t count (5.449) > t passive count (3.500) which, in other words, the active recovery has bigger effect than passive recover